Work stress among newly graduated nurses in relation to workplace and clinical group supervision. (25th November 2014) - Blomberg, Karin; Isaksson, Ann‐Kristin; Allvin, Renée; Bisholt, Birgitta; Ewertsson, Mona; Kullén Engström, Agneta; Ohlsson, Ulla; Sundler Johansson, Annelie; Gustafsson, Margareta
Abstract : Aim: The aim was to investigate occupational stress among newly graduated nurses in relation to the workplace and clinical group supervision. Background: Being a newly graduated nurse is particularly stressful. What remains unclear is whether the workplace and clinical group supervision affect the stress. Method: A cross‐sectional comparative study was performed in 2012. Data were collected by means of a numerical scale measuring occupational stress, questions about workplace and clinical group supervision. One hundred and thirteen nurses who had recently graduated from three Swedish universities were included in the study. Results: The stress was high among the newly graduated nurses but it differed significantly between workplaces, surgical departments generating the most stress. Nurses who had received clinical group supervision reported significantly less stress. The stress between workplaces remained significant also when participation in clinical group supervision was taken into account. Conclusions: Newly graduated nurses experience great stress and need support, especially those in surgical departments. Nurses participating in clinical group supervision reported significantly less stress. Implications for nursing management: It is important to develop strategies that help to adapt the work situation so as to give nurses the necessary support. Clinical group supervision should be considered as an option for reducing stress.